Religion, religiosity and slack creation: some empirical evidence / Shayuti Mohamed Adnan, Maliah Sulaiman - Mohamed Adnan, Shayuti (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2006)
Given that the ethical paradigms and the personal characteristics of managers serve as internally mediated controls for slack creation, our study examines if religion and religiosity influence the propensity of managers to create budgetary slack. We focus on Islam primarily because Islam does not recognize the divide between religious and worldly affairs. Accordingly, we argue that Islam may influence a manager's propensity to create slack. Data was collected using a questionnaire survey. To control for variation effects, questionnaires were sent to 91 managers of just one company, a Malaysian based Korean company. We found no significant difference between the slack created by Muslim and non-Muslim managers.